Functional characterisation of a soybean galactinol synthase gene under various stress conditions - Duc Ha Chu; Buffel Melanie; Tien Dung Le (Vietnam Journal of Science, Technology and Engineering, 2018)
Galactinol synthase (GolS) has been known to play a key role in raffinose biosynthesis by catalysing the formation of galactinol. The GolS gene family has been recently identified in various plant species. Among them, many individual GolS genes have been reported to function in plant stress tolerance. In this study, we reported the construction of transgenic Arabidopsis overexpressing a soybean GolS gene, GolS2. There were no significant differences in the phenotypes of the transgenic and control plants during normal physiological conditions. We evaluated the performance of the transgenic plants under various stress conditions in relation to that of the control plants. The result evidenced that the overexpression of GmGolS2 gene in Arabidopsis improved the plant’s tolerance to salt stress but did not protect the plants against heavy metals and paraquat. Our study suggested that soybean GolS genes could be a potential candidate for genetic engineering to improve abiotic stress tolerance of plants.